1989
DOI: 10.1063/1.101525
|View full text |Cite
|
Sign up to set email alerts
|

High current density in bulk YBa2Cu3Ox superconductor

Abstract: A liquid phase processing method for the fabrication of bulk YBa2Cu3Ox superconductors with large current carrying capacity has been developed. Slow cooling through the peritectic transformation (1030–980 °C) has been shown to control the microstructure of these superconductors. A cooling rate of 1 °C/h in this temperature range has yielded a microstructure with long plate type, thick grains oriented over a wide area. Current density up to 18 500 A/cm2 has been obtained by continuous direct current measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
135
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 767 publications
(144 citation statements)
references
References 6 publications
0
135
0
3
Order By: Relevance
“…This is easily seen in FIGURE 3 where all the elements increase in atomic % with increasing size, or increasing W atomic % except Cu, which instead decreases. It is widely observed in melt-textured YBCO superconductor that large deposits (up to several hundred micrometers in size) of a compound rich in Ba and Cu is a byproduct of the texturing process, e.g., [1][2][3][4][5][6][8][9]. A similar analysis (not shown) of the (W +Pt)-doped samples also concluded that Cu is not a component of the W-Pt-Y-Ba-O particles.…”
Section: Microstructurementioning
confidence: 62%
See 1 more Smart Citation
“…This is easily seen in FIGURE 3 where all the elements increase in atomic % with increasing size, or increasing W atomic % except Cu, which instead decreases. It is widely observed in melt-textured YBCO superconductor that large deposits (up to several hundred micrometers in size) of a compound rich in Ba and Cu is a byproduct of the texturing process, e.g., [1][2][3][4][5][6][8][9]. A similar analysis (not shown) of the (W +Pt)-doped samples also concluded that Cu is not a component of the W-Pt-Y-Ba-O particles.…”
Section: Microstructurementioning
confidence: 62%
“…The ball-milled powders were pressed into cylindrical samples 1.9 cm in diameter, top-seeded with SmBa 2 Cu 3 O 7-δ (Sm123), and melt-textured using a slow cooling process [6]. Textured samples were subsequently annealed in flowing oxygen gas.…”
Section: Methodsmentioning
confidence: 99%
“…A YBa 2 Cu 3 O 7-y (YBCO) superconductor has a high superconducting critical temperature (T c ) of 93 K [1], and a high critical current density (J c ) at the magnetic fields [2][3][4]. The electric transport capacity of a YBCO superconductor is dependent on the microstructure, especially the size and density of the micro-defects present in the superconducting grain.…”
Section: Introductionmentioning
confidence: 99%
“…This has been achieved by, for instance, melt processing (1,2). This technique, however, only improves the current carrying capacity on a small length scale.…”
Section: Introductionmentioning
confidence: 99%